2013
DOI: 10.1515/roe-2013-0203
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Terrorist Activities on Foreign Direct Investment: Nonlinear Evidence from Turkey

Abstract: In this study, we examine the relationship between foreign direct investment (FDI) and terrorist incidents that took place in Turkey during the period 1991:12 to 2003:12. By doing so we contribute to the literature by allowing for a possible nonlinear relationship between terrorism and FDI. The data used to measure the intensity of terrorism were collected from a major newspaper of Turkey, and therefore is limited to the direct signals given to the market. Empirical evidence from both linear and non-linear mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…These risks have been largely felt by Turkish SMEs in recent years. Turkey has been in close proximity to a number of regional conflicts with potential impacts on the SMEs (Omay et al 2013;Bilgel and Karahasan 2017) and because of their vulnerability (Pascual-Ramsay 2015) and awareness of these risks, such risks are perceived highly both in terms of the likelihoods and the impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risks have been largely felt by Turkish SMEs in recent years. Turkey has been in close proximity to a number of regional conflicts with potential impacts on the SMEs (Omay et al 2013;Bilgel and Karahasan 2017) and because of their vulnerability (Pascual-Ramsay 2015) and awareness of these risks, such risks are perceived highly both in terms of the likelihoods and the impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Bilgel and Karahasan (2017) found that after the rise of terrorism, the per capita real GDP in Eastern and Southeastern Anatolia declined by about 6.6%. Other studies also found that terrorism has a major negative impact on foreign direct investments in Turkey (Omay et al 2013).…”
Section: Small and Medium Enterprises And Global Geopolitical Risksmentioning
confidence: 94%
“…The PKK deliberately targets dams, power plants, irrigation networks, etc. Therefore, separatist terrorism has some other direct or indirect effects on economy (Özsoy and Şahin, 2006;Araz-Takay, Arin, and Omay, 2009;Ocal and Yildirim, 2010;Omay, Takay, and Ilalan, 2011).…”
Section: Inequality and Politics Of Separatism In Turkeymentioning
confidence: 99%
“…Mainly, we carried out diagnostic tests for skewness and kurtosis, autoregressive conditional heteroskedasticity (ARCH) test of Engle (1982), and the LM tests for autocorrelation, parameter constancy, and additive nonlinearity, as suggested by Eitrheim and Terasvirta (1996). If the estimated model passes all these 4 For other details involved in the estimation and evaluation phases, the researchers can read Teräsvirta and Anderson (1992), Hasanov and Omay (2008) and Omay et al (2013) diagnostic tests, then it can be employed for descriptive and/or forecasting purposes as we mentioned above.…”
Section: The Econometric Model Data and Empirical Resultsmentioning
confidence: 99%